2016
DOI: 10.1038/srep37484
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Exposure to Sound Vibrations Lead to Transcriptomic, Proteomic and Hormonal Changes in Arabidopsis

Abstract: Scientific Reports 6: Article number: 33370; published online: 26 September 2016; updated: 24 November 2016

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These findings can be attributed to sound-mediated photosynthesis-related gene expression and increased CO 2 fixation. A similar study showed that the expression of genes in the Gene Ontology categories mechano-stimulus responsive, signaling related, redox homeostasis, biosynthesis, and defense increased in response to exposure to 500 Hz sound waves in Arabidopsis ( Ghosh et al, 2016 ) ( Table 1 ). These results imply that sound vibrations provide a stimulus to plants.…”
Section: Production (Speaking) and Perception (Listening) Of Sound Inmentioning
confidence: 82%
See 4 more Smart Citations
“…These findings can be attributed to sound-mediated photosynthesis-related gene expression and increased CO 2 fixation. A similar study showed that the expression of genes in the Gene Ontology categories mechano-stimulus responsive, signaling related, redox homeostasis, biosynthesis, and defense increased in response to exposure to 500 Hz sound waves in Arabidopsis ( Ghosh et al, 2016 ) ( Table 1 ). These results imply that sound vibrations provide a stimulus to plants.…”
Section: Production (Speaking) and Perception (Listening) Of Sound Inmentioning
confidence: 82%
“…Exposing plants to sound activates plant innate immunity and (more specifically) elicits representative SA and JA defense signaling pathways similar to those observed in response to different chemical triggers ( Ghosh et al, 2016 ). Meta-analyses have demonstrated the occurrence of sound-mediated plant protection through the activation of the systemic immune response in crop plants such as pepper, cucumber, tomato, and strawberry ( Hou et al, 2009 ; Chowdhury et al, 2014 ; Mishra et al, 2016 ; Choi et al, 2017 ) ( Figure 2 ).…”
Section: Application Of Sound Waves To Improve Plant Healthmentioning
confidence: 84%
See 3 more Smart Citations